Awareness of Millennial Undergraduate Students of a Private University in the Philippines on Bioethical Practices and Issues - Gina Alvarado (Philippine Association of Institutions for Research, Inc., 2019)
This descriptive research assessed the level of awareness of millennial undergraduate students of a private university in the Philippines on bioethical practices such as abortion, surrogacy, euthanasia, eugenics, organ donation/ transplant, and in-vitro fertilization that give rise to bioethical issues. The author utilized a validated self-made instrument to gauge the respondents' knowledge, understanding, and awareness of these bioethical practices and issues. The findings show that all the student-respondents have a high level of knowledge that bioethical practices, such as abortion, surrogacy, eugenics, organ donation, and in-vitro fertilization do exist in modern society. They also reveal that Psychology, Education, and Nursing student-respondents have a very high level of understanding of the meaning of these bioethical practices. The results further reveal that Education students are the most highly aware of how the advancements in science lead to the emergence of new bioethical issues. The implications reflect the views of the millennial undergraduate students on the bioethical issues brought about by the advancements in medical science.  The millennial cohorts are the driving force shaping the future; hence, there is still a need to reinforce and develop the understanding of bioethics as respect for life which can help them make ethical choices in the dilemmas that they may face in life.